Kekuatan Bending dan Tarik Komposit Berpenguat Serat Eceng Gondok/Tebu Bermatrik Epoxy - Widodo, Rahmat Doni; Sutanto, Herry; Fitriana, Deni Fajar; Rusiyanto, Rusiyanto; Darsono, Febri Budi (Jurnal Rekayasa Mesin, 2024)
The use of natural fiber as composite material is growing rapidly due to excellent characteristics, environmentally friendly quality and low price. For this reason, natural fiber breaks the dominance of synthetic fiber composite previously used in industries, especially in automotive manufacturing. The purpose of this study is to determine the effect of fiber orientation on the flexural and tensile strength of water hyacinth-sugarcane fiber composite with epoxy matrix. The composite then be tested as an alternative to doortrim. Fiber orientation applied to specimens was random for sugarcane fiber, but continuous on water hyacinth fiber with angle variants of -45/45, 45/90, 45/45, and 90/90. Specimen standard for flexural test is ASTM D790-15 and ASTM D638-14 for tensile test. The study results show that the highest average value for flexural strength is 51.7 MPa of the 45/90 variant, while the lowest average value of 16.6 MPa is the 45/45 variant. Both 45/90 and -45/45 variants have the highest tensile strength of 30 MPa. The 90/90 variant records the weakest tensil strength value of 20 MPa. The highest flexural and tensile strength values exceed minimum score of the SNI 01-4449-2006 and equal the values of panel assy backdoortrim. This experiment proves that fiber orientation affects mechanical properties of composite materials, especially in terms of flexural or tensile strength.